Estudo palinológico da Vereda do Juquinha/Cuba, Parque Estadual da Serra do Cabral, Minas Gerais, Brasil - Gabriela Luiza Pereira Pires (2014)
Organic sediments rich in palynomorphs, as the ones studied in Juquinha/Cuba palm swamp, in Serra do Cabral, Minas Gerais State, can be an important parameter to reconstruct paleoenvironment evolution. This study presents the qualitative and quantitative pollen analysis of 35 stratigraphic levels from a core sample of 400 cm length corresponding to the last 18.486 years cal. BP. Regarding to the climatic changes a colder and wetter climate was registered between 18.486 years cal. BP and 8.276 years cal. BP. and a wetter climate with increase in temperatures from 7.828 years cal. BP to the present days. Three different intervals called JCI, JCII e JCIII were established based on palynological changes along the core: interval JCI with colder and wetter climatic conditions, between 18.486 years cal. BP and 8.276 years cal. BP recording Podocarpus, Drymis brasiliensis, Eryngium, Hydrocotyle e Peperonia taxa; interval JCII from 7.134 years cal. BP to 2.924 years cal. BP, with the increase in humidity, temperature and taxa diversity and the first occurrence of Mauritia flexuosa at 4.226 years cal. BP, the palm swamp in these interval was surrounded by a mosaic of Cerrado (broad sense) and forests; interval JCIII with higher humidity conditions such as JCII conditions but with palm swamp expansion and mosaic of Cerrado (broad sense) and forests decrease.